Sensor-guided jogging for visually impaired - Ramer, Christina; Ziegler, Christian; Reitelshöfer, Sebastian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
This paper introduces an approach for enabling visually impaired and blind people to practice jogging activities by 3D environment perception for course detection and collision avoidance, as well as feedback generation in an intuitive manner. Besides a system concept, first prototypic realizations, that confirm the general feasibility, are presented for this domain, which has not been addressed by research until now.
Keywords: handicapped aids; object detection; optical sensors; 3D environment perception; blind people; collision avoidance; course detection; feedback generation; optical sensors; sensor-guided jogging; visually impaired people; Belts; Cameras; Navigation; Sensors; Standards; Three-dimensional displays; Visualization